Power-sharing and Identity-Politics Transformation in Zanzibar, Tanzania - Moh'd Haji (African Journal of Political Science)
Zanzibar has had a long unsettled political history from its colonial era to radicalized post-colonial politics. The core source of such politics is the cosmopolitan nature of the isles whereby races and identities reside on the island for a long time. Such nature made the political and social groups categorized and differentiated from others through identity. As a result, the struggle for the owner and ruler of the island becomes a high concern among the groups in the society. This situation resulted in turbulent politics for many years with violence, killings, and hostility. In 2010, Zanzibar inters in the negotiation to solve the political problem that marred the island for a long time. The Government of National Unity (GNU) which involves the sharing of power between the first and second winners was agreed upon as the structure of the leadership style of Zanzibar. This was done through referendum and constitution amendment. As political identity theory reveals that; political elites use identity groups for their political benefits. They organized and influence their political activities through the identity they are familiar with. So, in solving such an identity politics problem, the identity tragedy must be transformed and accommodated the rational politics. This paper seeks to examine the extent to which power-sharing transforms identity-based politics and is accommodated in Zanzibar. The study was conducted in three districts to represent Zanzibar. Both qualitative and quantitative data were collected from five in-depth interviews and two hundreds and eight seven questionnaires respectively. The in-depth interviews involved the GNU's current and former top leaders, members of the Cabinets, and political activists.  The questionnaire involves the citizens from districts Mjini, Micheweni, and Kusini.  The study found that to some extent the power-sharing successes in reducing the exercises of identity politics in Zanzibar. Three angles have been justifying that reduction. First is the existence and increase of political trust in society to large extent. The second one is the equal treatment of all identity groups, races, and regions by government institutions and society. The Last one is the exercises of political activities without the influence of historical and identity political narrations. This study pinpoints two important aspects of transformational identity politics through power-sharing. The first one is the role of leadership in transforming the mindset and bringing people together. The second one is social change due to generations' natural changes and opportunities. The study concludes that power-sharing can be the source of identity transformation from worst uses to recognition in the society. This will happen only if the power-sharing institution is set to consider the potentiality of mutual recognition of self and respecting social, cultural, and ideological differences in society.